PENGARUH KUALITAS KOMUNIKASI ATASAN-BAWAHAN TERHADAP KINEJA PEGAWAI PADA KOPERASI SIMPAN PINJAM BALO’ TORAJA - Ferdanto, Handir; Ocky Sundari (Media Ekonomi, 2023)
This study aims to determine the effect of the quality of superior-subordinate communication on the performance of employees of the Balo' Toraja Savings and Loans Cooperative. This research uses a quantitative type of research, by first conducting an instrument test. The data used is primary data obtained by distributing questionnaires to objects in 2023. The analysis uses the t-test to see the effect of the variable quality of superior-subordinate communication on employee performance. The results of the study found that the quality of superior-subordinate communication affects employee performance at the Balo' Toraja Savings and Loans Cooperative.